Comparing the importance of farming resource endowments and agricultural livelihood diversification for agricultural sustainability from the perspective of the food–energy–water nexus. (20th December 2022) - Peng, Wenjia; Zheng, Hua; Robinson, Brian E.; Li, Cong; Li, Ruonan
Abstract: Sustainable agricultural development, which aims to optimize income and minimize resource consumption and environmental impacts, is strongly influenced by farming resource endowments and agricultural livelihood strategies. However, quantifying the impacts of these factors on agricultural sustainability remains a challenge. Here, we proposed a framework that incorporated the agricultural food–energy–water (FEW) nexus into a sustainable livelihood framework, to explore agricultural sustainability. We then applied a partial least squares–structural equation model (PLS-SEM), based on household survey data from MiYun Reservoir watershed, China, to identify the complex pathways of the impact of household farming resource endowments and livelihood diversification on agricultural sustainability. Our study indicated that diversified farming achieved a better performance in the FEW nexus via the mediating factor of farming inputs (β = 0.335, p < 0.01). Meanwhile, diversified farming had positive effects on economic profits and environmental sustainability (β = 0.531, p < 0.01). Increasing farming resource endowments also had a better performance in the FEW nexus (β = 0.211, p < 0.01); however, that may lead to economic and environmental costs (β = −0.445, p < 0.01). The framework can be used to identify the relationship between household livelihoods and the FEW nexus to better achieve resource security and sustainable development goals. Graphical abstract: Image 1 Highlights: Resource endowments and livelihood diversification impact agro-sustainability. Sustainability can be quantified by food–energy–water (FEW) nexus approach. New framework incorporates the FEW nexus into a sustainable livelihood framework. The framework quantified resource endowments and farming diversification impacts. Diversified farming improves agro-sustainability by strengthening the FEW nexus.